Stress Levels and Sleep Disorders among Undergraduate Nursing Students During COVID-19 Pandemic: A Cross-Sectional Study from Indonesia - Raini Diah Susanti; Citra Windani Mambang Sari; Sherie Meiza Dania Lauren; Mamat Lukman; Aep Maulid Mulyana (Universitas Padjadjaran, 2022)
The COVID-19 pandemic has forced universities to change their teaching and learning activities using online methods, which can impact students' stress problems, including undergraduate nursing students. This study aims to identify the relationship between stress levels and sleep disorders among nursing students in online learning during the COVID-19 pandemic. A cross-sectional study included 253 nursing students from the Faculty of Nursing at Universitas Padjadjaran between 2018 and 2021, and completed the Student Nurse Stress Index (SNSI) questionnaire and the Pittsburgh Sleep Quality Index (PSQI) questionnaire from June 2022 to July 2022. Study findings, all individuals reported experiencing moderate to severe stress levels and had an impact on sleep disorders, with a sig. (2-tailed) namely 0.001 (<0.05) and correlation (r) 0.290. The majority reported moderate stress, i.e. less disturbed sleep (70.6%), disturbed (63.2%), and very disturbed (52.6%). Meanwhile, severe stress, namely disturbed sleep (33%) and very disturbed (47.4%). Although, there were 14.3% had mild stress and slept less disturbed. The highest levels of stress and sleep disorders were reported by women (85.4%), 17-21 years old (78.7%), and lived with their family (77.1%). This study highlights that the COVID-19 pandemic related to stress and sleep disorders has a significant relationship. Therefore, future studies using meta-regression are needed to investigate the factors influencing and exacerbating stress and sleep disorder among nursing students in online learning during the COVID-19 pandemic to minimize results bias.